Project x: is dad in here? - Lane, Alex; Bartlett, Alison (Oxford University Press UK, 2009)
"Project X: Is Dad in Here?" is a thrilling mystery novel that follows a group of teenagers as they investigate the disappearance of their friend's father. This fast-paced book is full of suspense and twists and turns, keeping readers hooked until the very end. The story explores themes of friendship, loyalty, and the importance of family.